2022
DOI: 10.4317/medoral.25013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the prevalence of impacted third molars and the effects of eruption level and angulation on caries development by panoramic radiographs

Abstract: Background This study is aimed to determine the prevalence of impacted third molars and to investigate the effects of their eruption level and angulation on caries formation in the distal of the adjacent tooth. Material and Methods This cross-sectional study was conducted on panoramic radiographs of 38481 patients who were admitted to the Trakya University, Faculty of Dentistry. The panoramic radiographs of 7998 patients with at least one impacted third molar were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
(39 reference statements)
0
4
0
1
Order By: Relevance
“…Hashemipour et al . [ 9 ] research revealed that the extent of impacted 3 rd molars in Iran was estimated at 44.3%, Yıldırım and Büyükgöze-Dindar[ 10 ] research found 23% incidence, but Hattab et al . [ 11 ] study found it was 33%.…”
Section: Discussionmentioning
confidence: 99%
“…Hashemipour et al . [ 9 ] research revealed that the extent of impacted 3 rd molars in Iran was estimated at 44.3%, Yıldırım and Büyükgöze-Dindar[ 10 ] research found 23% incidence, but Hattab et al . [ 11 ] study found it was 33%.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of impacted teeth was extensively investigated, and researchers showed that third molars would compromise the most common type of impaction. 9 , 10 , 11 In KSA, third molar impaction was mostly found in Riyadh province that is centrally situated. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ideally all impacted third molar should be removed, unless contraindicated. [12][13][14][15] Based on gender (Table 2), the numbers of patients with impacted teeth both before and during the pandemic were 452 (63.3%) and 385 (66.6%), and were dominated by females. The study conducted in Kuwaiti by Ali, et al, 7 had the same results too, from a total of 932 cases there were 411 (44%) males and 521 (56%) females.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ideally all impacted third molar should be removed, unless contraindicated. [12][13][14][15] The frequent indication of third molar removal is pericoronitis, dental caries, orthodontic treatment, periodontal disease, facial pain, root resorption and odontogenic cyst and tumour, and pain of unexplained origin. [16][17][18][19][20] The high prevalence of impacted teeth and the COVID-19 pandemic interest the authors in seeking more information about this.…”
Section: Introductionmentioning
confidence: 99%